2000
DOI: 10.1007/s002160000536
|View full text |Cite
|
Sign up to set email alerts
|

Ion chromatography inductively coupled plasma mass spectrometry (IC-ICP-MS) and radiometric techniques for the determination of actinides in aqueous leachate solutions from uranium oxide

Abstract: The choice of the analytical method for the determination of actinide isotopes in leachate solutions has to be made considering several parameters: detection limit for each isotope, sample preparation procedure in terms of duration and complexity, counting time and interferences. A leachate solution obtained by keeping a pellet of UO2 doped with 238Pu in contact with distilled water was investigated for the content of U and Pu isotopes by radiometric methods (alpha-, gamma-spectrometry and liquid scintillation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…It was found that the addition of DAP as an organic complexing agent to the eluent improved the peak resolution and avoided column ageing. Under the same separation conditions Solatie et al21 obtained a high recovery (96-98%) at ng mL À1 concentration level of Pu.In comparison with the CS10 column method, an anionic/ cationic mixed bed chromatographic column (CS5A) drastically improved chromatographic resolution based on the large difference (60 min) in the retention times between Pu and U, in which 100 mM H 2 C 2 O 4 in 190 mM LiOH and 2 M HCl was employed as an eluent(Perna et al 22 ). Moreover, the replacement of 0.2 M NaNO 2 with AgO for the oxidation of Pu avoids contamination of the system with silver.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…It was found that the addition of DAP as an organic complexing agent to the eluent improved the peak resolution and avoided column ageing. Under the same separation conditions Solatie et al21 obtained a high recovery (96-98%) at ng mL À1 concentration level of Pu.In comparison with the CS10 column method, an anionic/ cationic mixed bed chromatographic column (CS5A) drastically improved chromatographic resolution based on the large difference (60 min) in the retention times between Pu and U, in which 100 mM H 2 C 2 O 4 in 190 mM LiOH and 2 M HCl was employed as an eluent(Perna et al 22 ). Moreover, the replacement of 0.2 M NaNO 2 with AgO for the oxidation of Pu avoids contamination of the system with silver.…”
mentioning
confidence: 82%
“…Pu is generally converted to the +4 oxidation state in most of the chromatographic methods (except for a few cases 20,21,57 ), and then is eluted from resin or solvent by reduction to the +3 oxidation state.…”
Section: Adjustment Of Pu Oxidation Statementioning
confidence: 99%
“…Isotope speciation is very important in environmental radiochemistry for understanding transfer/migration mechanisms [20,21] and age determinations [22] and bioavailability [23,24]. The complete record of fission products and actinides can be obtained using, mass spectrometry (very good detection limits) as compared to radiometric methods [25][26][27][28][29]. Due to peculiar physical and geochemical reasons the Pu concentration reaches 10 -12 to 10 -13 g/g in soils of the Northern hemisphere [30] but the concentrations would be higher in the regions contaminated with accidental fallout from nuclear reprocessing plants and nuclear power plants, e.g.…”
Section: Applications In Nuclear Industrymentioning
confidence: 99%
“…The subsequent separations were performed to purify the obtained U-fraction from remaining Pu using UTEVA resin, and the Pu-fraction was decontaminated from residual Cm using Dowex anion exchanger. After the chemical separations the purified U-fraction and Pu-fraction were electro-deposited using the (NH 4 ) 2 C 2 O 4 /HCl method [4].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Only 238 Pu is routinely determined by α-spectrometry. Due to the relatively small amounts of 232 U and 236 Pu in the fuel and their short half-lives, it is more advantageous to use radiometric methods, namely α-spectrometry and liquid scintillation counting (LSC) [4]. A chemical separation is required beBrought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 5/28/15 2:39 PM fore the instrumental measurement.…”
Section: Introductionmentioning
confidence: 99%